National interests and supranational resolution in the European Banking Union - Tobias Tröger; Anastasia Kotovskaia (Leibniz Institute for Financial Research SAFE, 2022)
We investigate whether the bank crisis management framework of the European banking union can effectively bar the detrimental influence of national interests in cross-border bank failures. We find that both the internal governance structure and decision making procedure of the Single Resolution Board (SRB) and the interplay between the SRB and national resolution authorities in the implementation of supranationally devised resolution schemes provide inroads that allow opposing national interests to obstruct supranational resolution. We also show that the Single Resolution Fund (SRG), even after the ratification of the reform of the European Stability Mechanism (ESM) and the introduction of the SRF backstop facility, is inapt to overcome these frictions. We propose a full supranationalization of resolution decision making. This would allow European authorities in charge of bank crisis management to operate autonomously and achieve socially optimal outcomes beyond national borders.
Keywords: G01; G18; G21; G28; K22; K23; 330; SRB; SRF; bank resolution; banking union; bail-in; ESM; national interest; political economy; bureaucrats' incentives